2006
DOI: 10.1111/j.1471-4159.2006.03986.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic resistance of neural stem cells to toxic metabolites may make them well suited for cell non‐autonomous disorders: evidence from a mouse model of Krabbe leukodystrophy

Abstract: While transplanted neural stem cells (NSCs) have been shown to hold promise for cell replacement in models of a number of neurological disorders, these examples have typically been under conditions where the host cells become dysfunctional due to a cell autonomous etiology, i.e. a 'sick' cell within a relatively supportive environment. It has long been held that cell replacement in a toxic milieu would not likely be possible; donor cells would succumb in much the same way as endogenous cells had. Many metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 45 publications
0
48
0
1
Order By: Relevance
“…23,24 The results suggest that NPC could attenuate damage to motor functions. Transplanted mouse NPC or gene-modified NPC (overexpressed β-galactocerebrosidase [GALC]) could survive for a long time in the brain of a globoid cell leukodystrophy mouse model, produce functional GALC and enhance the enzyme activity in the brain and spinal cord, reduce accumulation of galactocerebroside, delay symptom onset, and extend their life spans to 2-3 times longer than expected.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…23,24 The results suggest that NPC could attenuate damage to motor functions. Transplanted mouse NPC or gene-modified NPC (overexpressed β-galactocerebrosidase [GALC]) could survive for a long time in the brain of a globoid cell leukodystrophy mouse model, produce functional GALC and enhance the enzyme activity in the brain and spinal cord, reduce accumulation of galactocerebroside, delay symptom onset, and extend their life spans to 2-3 times longer than expected.…”
mentioning
confidence: 76%
“…24 No transplantation-related severe adverse events occurred during the study. Shihabuddin et al 22 found that many sites within the brain transplantation of adult mouse NPC with the overexpressed acid sphingomyelinase gene (ASM) into the Niemann-Pick-A mouse (ASM gene knocked out) led to a marked regional decrease in free cholesterol and sphingomyelin storage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This would seem to match the likely scenario well in treating children with leukodystrophies. However, transplantation of OPCs has also been carried out in adult shi mice [78][79][80] and in the sh pup [52] with successful myelination. This is not always true in all of the myelin mutants, as we and others have had little success in transplanting OPCs into the CNS of the taiep rat.…”
Section: Myelinationmentioning
confidence: 99%
“…6). In 1 study, a neural stem cell line genetically modified to overproduce GALC was transplanted into the twi brain [78]. The donor cells appeared to have migrated, proliferated, and finally distributed widely in the brain, although the proportion of donor cells that differentiated into myelinating OLs is unclear.…”
Section: Transplantation Of Cells Into the Twi Mousementioning
confidence: 99%